Optimizing conditions for augmented production of amylase by Talaromyces islandicus AUMC 11391 - Osama A.M. Al-Bedak; Ahmed M. Moharram; Fuad Ameen; Steven L. Stephenson; Marwa M.M. Idres; Manal M. Yasser (Electronic Journal of Biotechnology)
Background: To satisfy rising biotechnological needs, climate change, and depleting water supplies, amylases that can survive high temperatures, and salt concentrations must be developed. Amylases are the most important enzymes that comprise approximately 25–33% of the international enzyme market and have a great role in many industries. Results: In this investigation, Talaromyces islandicus AUMC 11391 was used to produce amylase in submerged fermentation (SmF) in an augmented concentration of 232 ± 36 U/mL after 8 d of incubation at pH 6.0 and 30°C using sodium nitrate as a nitrogen supply. The obtained enzyme was partly purified employing 70% ammonium sulfate and then dialysis. The activity of the produced amylase exhibited reached the peak (992.14 ± 80 U/mg protein) at pH 5.0 and 55°C. Cu, Co, Fe, Ni, Ca, and Zn had an activating effect on the activity of the amylase enzyme at pH 5.0 and 55°C by 134.57, 123.1, 115.4, 109.76, 105.43, and 103.2%, respectively. The Km and Vmax were recorded as 132.1 mM and 60.6 µmol/min, respectively. T. islandicus AUMC 11391′s-amylase hydrolyzed the raw starch of maize, sorghum, wheat, rice, and oat at rates of 12.3, 113.7, 32.25, 34.67, and 73.6% in contrast to the soluble starch. Conclusions: This enhanced α-amylase from T. islandicus AUMC 11391 looks to be a potential option to meet the present amylase requirements of a variety of industrial processes because of its improved production and beneficial properties.How to cite: Al - Bedak O.A.M., Moharram AM., Ameen F, et al. Optimizing conditions for augmented production of amylase by Talaromyces islandicus AUMC 11391. Electron J Biotechnol 2025;75. https://doi.org/10.1016/j.ejbt.2025.01.008.